PENGARUH ECONOMIC VALUE ADDED (EVA), RETURN ON INVESTMENT (ROI), CURRENT RATIO (CR) DAN PRICE TO BOOK VALUE (PBV) TERHADAP HARGA SAHAM - Nurlaelah; Firmansyah; Ulfah Mualafah (Universitas La Tansa Mashiro, 2024)
The share price is the price of shares on the stock exchange which is a consideration for investors before investing in a company. Before investing in a company, investors should conduct a fundamental analysis. This study aims to test and analyze the effect of Economic Value Added (PBV), Return On Investment (ROI), Current Ratio (CR) and Price to Book Value (PBV) on Stock Prices in Primary Consumer Sector Companies Listed on the Indonesia Stock Exchange for the period 2018-2022. The method used is quantitative method. The sample of this study amounted to 22 Primary Consumer Sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period which had been eliminated using purposive sampling technique. The analysis technique used is multiple linear regression analysis techniques using the SPSS V.23 program. The results showed that Economic Value Added, Return On Investment and Price to Book Value partially each had a positive and significant effect on Stock Prices. while Current Ratio partially has no effect on Stock Prices. As for the simultaneous test, Economic Value Added, Return On Investment, Current Ratio and Price to Book Value together have an effect on Stock Prices